Critical Health Communication Methods: Challenges in Researching Transformative Social Change - Zoller, Heather M. (Frontiers in Communication, 2019)
This reflexive essay describes how methodological choices involved with critical commitments to understanding the economic and political roots of health status lead to challenges in the field that intersect with the politics of academic training, visibility, and publishing. Through the lens of my own research experiences, I discuss lessons learned as well as ways that I continue to struggle. I consider issues that are primarily personal and those that we should address as a field. In the essay, I describe six observations from my experiences researching transformative social change that have implications for critical health communication scholars and the discipline of health communication.